1982
DOI: 10.1159/000212511
|View full text |Cite
|
Sign up to set email alerts
|

Hydergine in Senile Mental Impairment

Abstract: Among gerontopsychiatric drugs, Hydergine is pharmacologically characterized by agonist action at central dopamine and serotonin receptors. This review presents a summary of the results obtained with Hydergine in numerous controlled trials in patients with senile mental impairment. Assessment was carried out by means of a rating scale (mainly the Sandoz Clinical Assessment Geriatric, or SCAG, scale), psychometric tests (e.g. the Nuremberg Geriatric Inventory, or NGI), and the EEG. Hydergine also lowers serum p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“… Failure to come back ( 3 ), exitus for heart failure ( 2 ), patient's refusal for gastric pain and hot flushes ( 1 ). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Failure to come back ( 3 ), exitus for heart failure ( 2 ), patient's refusal for gastric pain and hot flushes ( 1 ). …”
Section: Resultsmentioning
confidence: 99%
“…D espite ample evidence of a real, though limited, effectiveness of ergot derivatives in senile mental deterioration, 1–5 there seems still to be a rather diffuse impression among clinicians and clinical pharmacologists that these compounds are of little use and work no more than a placebo 6 . Wittily, Goodwin and Goodwin 7 referred to these compounds as an example of the so‐called “tomato effect.” Indirectly contributing to this concept are speculations that the daily doses in most trials might have been too low or the duration of treatment too short 8 .…”
mentioning
confidence: 99%
“…The basic pharmacodynamic profile of co-dergocrine mesylate has been demonstrated in numerous experimental studies (Loew et al 1980;Loew & Weil 1982;Markstein 1985;Spagnoli & Tognoni 1983;Weil 1988). However, the mechanism of action of co-dergocrine mesylate has yet to be established conclusively.…”
Section: Pharmacodynamic Propertiesmentioning
confidence: 97%
“…The ergoloid mesylates have been available for the past three decades. Though originally manufactured as a vasodilator, Hydergine (a combination of the ergoloid mesylates) was found to affect the serotonin and dopamine systems as an agonist (Loew and Weil, 1982). There continue to be reports of its efficacy in treating dementia (McDonald and Krishnan, 1990), but studies (Thompson and others, 1990) have found Hydergine ineffective in treating Alzheimer's disease.…”
Section: Treatmentmentioning
confidence: 99%